Problems of forecasting demand for working force in the labor market in Kazakhstan - Джумамбаев, С. (Journal of Economic Research & Business Administration, 2019)
The condition for the successful implementation of the third modernization of Kazakhstan is to ensure the effective functioning of the labor market. The current model of the Kazakhstan labor market has largely exhausted its potential as a driver of economic growth. Its modernization, taking into account the experience of the developed countries of the world and the peculiarities of the country’s development, will make it possible to carry out a more accurate forecast of the parameters of the labor market, including the demand for labor. This problem is not given due attention by domestic science and practice. The goal of the article is to adapt modern methodological tools for analyzing and forecasting the demand for labor to Kazakhstani data. The features of the socio-economic development of the country in terms of their impact on the quantitative side of the demand for labor are considered, the choice of the main factors influencing the change in employment is made, the economic-mathematical model for predicting the demand for labor is derived. The applied research methodology allowed for the first time in Kazakhstan to establish and assess the dominant influence on employment change of two macroeconomic factors: the dynamics of GDP and investment. Practical significance: the results of the study can be used in the future to analyze and predict the demand for labor. The necessity of creating a labor research institute (center) funded from the state budget is substantiated.